ETHNIC IDENTITY AND ELECTORAL POLITICS IN BIHAR: FROM INDEPENDENCE TO MANDAL'S POLITICS - Kumar, Pramod; Kumar, Sanjeev; Sharma, Dipika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper examines the dynamics of caste and identity politics from the era of post -independence in Bihar. This highlights the continuous role of caste in the socio-political changes and electoral behavior brought by the leaders of the backward caste and the historical development of caste-based political mobilization. This paper investigates major political movements and developments such as the rise of the Janata Dal and the establishment of the Mandal Commission report and their influence on the political scenario of Bihar. In the end the paper states that the politics of development oriented governance and caste -based identity dominates the political field of Bihar.